Clinical and immunologic abnormalities in COVID-19 - A. K. Karibova; S. S. Akhmedkhanov; M. T. Kudae; H. M. Malaev (Современная ревматология, 2024)
Objective: to find approaches to improve diagnostics of the debut of rheumatic manifestations, associated with COVID-19.Material and methods. Data from 1000 patients from the COVID-19 registry were included in the prospective cohort study. In all patients, the diagnosis of COVID-19 was confirmed by polymerase chain reaction. Of these patients, 380 (41.8% men and 58.2% women, mean age 47.0±2.5 years) had rheumatic manifestations. Patients were examined using routine clinical methods. Immunological markers of rheumatic diseases were determined, including antibodies against cyclic citrullinated peptide, rheumatoid factor, antiphospholipid antibodies and antinuclear factor (ANF), and an immunoblot for antinuclear antibodies was performed if ANF titer was >1:160.Results and discussion. Patients had the following rheumatic manifestations: arthralgias (in 342), myalgias (in 23), skin rashes (in 15). ANF titers >1:160 were found in 57.6% of patients. No reliable data indicating the development of an antiphospholipid syndrome were found in the study group. Lupus anticoagulant was detected in 5.7% of cases, antibodies against β2-glycoprotein in 5.7%, antibodies against cardiolipin in 3.8%. High ANF titers were found in 63.9% of patients with arthralgia. Gender-specific differences were found when analyzing the correlation between ANF titers and rheumatic manifestations: in men, high ANF tires were associated with myalgias, and in women with arthralgias. The presence of rheumatic manifestations depended directly on the severity of the disease. A correlation between arthralgia and leucopenia was also found – leucocyte count < 3,9 ‧109 /L was a predictor of arthralgias. The sensitivity and specificity of the model were 99.3 and 91.2%, respectively.Conclusion. The results suggest that COVID-19 can provoke the development of immunological abnormalities that may subsequently lead to the development of an autoimmune diseases (AID). The optimal approach to prevention and early detection of AID in patients with coronavirus infection caused by SARS-CoV-2 is to monitor laboratory parameters – leukocyte count and CRP level. If rheumatic manifestations are present, the use of immunological and imaging examinations is also recommended.